PEMANFAATAN LIMBAH CANGKANG KERANG DAN JERUK SUANGGI DI DESA OLELE SEBAGAI PASTA GIGI RAMAH LINGKUNGAN (BIALIMUDENT) - Margaretha Solang; Djuna Lamondo; Syam S Kumaji (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Cockle (or “bia” in Gorontalo language) and lime (“limu” in Gorontalo language) can be found in Olele village, which is located nearby Tomini bay. The objective of this community service program was to disseminate information regarding the chemical content of the shell of cockles and the addition of lemon extract as a preservative, which has the potential as an eco-friendly toothpaste, to society. Further, this program was also aimed at improving people’s skills in processing the two products. The program consisted of mentoring and training activities. It was revealed that the program improved the knowledge of the local community, especially fishermen’s wives and the participants of the program, regarding the content of calcium carbonate (CaCO3) within the shells of cockle at 12,254.64 mg/kg, which could be used as a material of natural, eco-friendly toothpaste. On top of that, the people were also aware of the utility of lime as a preservative material. This community service program received support from the governance of Olele village. Further follow-ups would be designed in the form of innovative village competition.  Keywords: Shells of cockles; lemon; society, toothpaste